2014
DOI: 10.1016/j.vaccine.2014.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Oral retinyl palmitate or retinoic acid corrects mucosal IgA responses toward an intranasal influenza virus vaccine in vitamin A deficient mice

Abstract: Vitamin A deficiency (VAD) is a leading cause of pediatric morbidity and mortality due to infectious diseases. Recent pre-clinical studies have revealed that VAD impairs mucosal IgAproducing antibody forming cell (AFC) responses toward a paramyxovirus vaccine in the upper respiratory tract (URT), thus impeding a first line of defense at the pathogen's point-of-entry. The studies described here tested the hypothesis that VAD may also impair immune responses after FluMist vaccinations. Results show that (i) IgA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 28 publications
(25 reference statements)
1
54
0
4
Order By: Relevance
“…We further found that vaccinated VAD mice were incompletely protected from invasive bacterial challenge, whereas the PCV-13 vaccine protected control mice. The poor response to PCV-13 vaccination observed in VAD mice complements previous studies of respiratory virus vaccines in the context of VAD whereby mucosal antibody responses were poor toward a parainfluenza virus (Sendai virus), a human influenza virus vaccine (FluMist), and a cold-adapted, PR8-derived influenza virus vaccine [10, 13]. Molrine et.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We further found that vaccinated VAD mice were incompletely protected from invasive bacterial challenge, whereas the PCV-13 vaccine protected control mice. The poor response to PCV-13 vaccination observed in VAD mice complements previous studies of respiratory virus vaccines in the context of VAD whereby mucosal antibody responses were poor toward a parainfluenza virus (Sendai virus), a human influenza virus vaccine (FluMist), and a cold-adapted, PR8-derived influenza virus vaccine [10, 13]. Molrine et.…”
Section: Discussionsupporting
confidence: 77%
“…Vitamin A deficiencies (VAD) and insufficiencies are present in both developed and developing countries [69] and have been associated with poor immune responses toward respiratory tract pathogens [10, 11], as well as an increased incidence of and morbidity from respiratory disease in school age children. Knowing that prevention of infection is critical in these highly susceptible populations, we employed a murine model of VAD to determine if PCV-13 was efficacious in the context of VAD.…”
Section: Introductionmentioning
confidence: 99%
“…Small animal studies previously showed that VAD is associated with poor IgA responses to respiratory viruses and that vitamin supplementation restores IgA responses (31, 35, 36). Apart from immunological deficiencies, VAD animals are characterized by a partial loss of cilia as well as squamous metaplasia within the epithelial lining of the respiratory tract (68).…”
Section: Discussionmentioning
confidence: 99%
“…Receptor proteins can bind promiscuously to ligands and to noncanonical DNA motifs. In some instances, vitamin receptors (and related members of the nuclear receptor superfamily) behave synergistically, but in other instances, they antagonize one another (e.g., vitamin D exerts a negative effect on the vitamin A-dependent commitment of bone marrow cells to the granulocytic lineage [13,[17][18][19][20] (23,24). These results have important clinical implications, as mucosal IgA may provide a first line of defense against infectious respiratory virus diseases in humans (25)(26)(27).…”
mentioning
confidence: 99%